AN ANALYSIS OF MORAL VALUE IN STATING THE PRINCIPLE IN “KICKBOXER” MOVIE - Bejo Sutrisno; Albert Situmorang (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2021)
The aims or this research are to analyze the moral values ​​and principles of moral values that are delivered in the "Kick boxer" movie. To strengthen this analysis, the qualitative research methods are used by using two data sources, namely primary and secondary data. Primary data is “kick boxer" movie, where the data are carefully recorded from the movie based on the problem formulation. Secondary data is taken from other sources related to the analysis, such as journals, e-books, and websites. Based on the analysis, the findings of moral values ​​are presented in: (1) Trustworthiness; (2) Respect; (3) Responsibility; (4) Fairness; (5) Caring and the principles of moral values ​​present are: (1) Respect for rules; (2) Avoidance of illicit Operation. Furthermore, from these findings too, that moral values ​​and the principles of moral values ​​are a way of human life that reflect good behaviors that are very important and valuable things in human social life, in terms of getting peace, mutual help, happiness, and good goals